Mapping Computational Thinking in the Era of Digital Transformation for Education toward SDG 4: A Bibliometric Analysis - Afra Lathifah; Adrie Satrio; Liana Mumrikoh (Universitas Sebelas Maret, 2026)
Computational Thinking (CT) has emerged as an important competency in education in response to ongoing digital transformation and the increasing emphasis on Sustainable Development Goal 4 (SDG 4). This study employs bibliometric analysis to examine CT-related publications from 2015 to 2025. Network, cluster, and overlay visualization techniques were used to identify key research trends, thematic developments, and collaboration patterns in the field. The results indicate a continuous growth in CT research and a shift from viewing CT primarily as a programming skill toward a broader cognitive and pedagogical construct involving problem solving, abstraction, and adaptive reasoning. CT is predominantly associated with workforce preparation, teacher capacity-building, and instructional innovation across educational contexts. While research has expanded into areas such as early childhood education and digital learning environments, topics related to equity, sustainability, and global citizenship remain relatively underexplored. Overall, this study highlights the evolving conceptualization of CT in education and underscores the need for more inclusive and sustainability-oriented research in future studies.